Facile Skeletal Rearrangement of Polycyclic Disilenes with Bicyclo[1.1.1]pentasilanyl Groups. Issue 44 (10th July 2018) - Yokouchi, Yuki; Ishida, Shintaro; Iwamoto, Takeaki
Abstract: The unexpected formations of fused polycyclic disilenes2 a and ( E ), ( Z )‐3 b by the reduction of the 1, 2‐dibromodisilanes5 a (R=Me) and5 b (R= i Pr) bearing bicyclo[1.1.1]pentasilanyl (BPS) groups is reported. The disilenes2 a and ( E ), ( Z )‐3 b were characterized by a combination of NMR spectroscopy and X‐ray diffraction analysis (XRD). The reduction of5 b in the presence of 2, 3‐dimethyl‐1, 3‐butadiene provided an ene adduct of the disilene1 b bearing BPS groups, which suggested that an initial product of the reduction of5 b was the disilene1 b . Thermal reactions of2 a and ( E ), ( Z )‐3 b afforded the highly strained saturated silicon clusters4 a and4 b . A computational study suggested that the transformation of1 to2, 3, or4 can involve silyldisilene–disilanylsilylene rearrangement reactions and insertion reactions of a silylene into a Si−Si bond. Abstract : Expect the unexpected : Reduction of a 1, 2‐dibromodisilane bearing highly strained bicyclo[1.1.1]pentasilane cages provided a disilene with a rearranged polycyclic silicon skeleton, which underwent further skeletal isomerization to afford a polycyclic oligosilane (see figure).